Clinical Symptoms of Patients with Early-Stage and Advanced-Stage Ovarian Cancer - Shofwana, Haura Almash Aulia; Hidayati, Hanik Badriyah; Saraswati, Wita; Tjokroprawiro, Brahmana Askandar (Indonesian Journal of Cancer, 2024)
Background: Ovarian cancer is a malignant neoplasm originating from ovarian cells with different histological types depending on the subtype. It can affect women of all ages. Ovarian cancer ranks third in terms of incidence among diagnosed female cancer patients, following breast and cervical cancer. Ovarian cancer often doesn’t present specific/clear symptoms. As a result, only a small number of patients are diagnosed at an early stage (20%). The study aimed to analyze the clinical complaints experienced by ovarian cancer patients, both in early and advanced stages before diagnosis. Methods: This descriptive cross-sectional study analyzes clinical complaints before the diagnosis of early and advanced-stage ovarian cancer patients. The study was conducted in the Gynecology-Oncology inpatient ward at Dr. Soetomo Regional General Hospital in 2021, utilizing medical record data. Results: A total of 98 patients (21 patients with early-stage, and 77 patients with advanced-stage) were analyzed. The majority of the patients are aged 45-58 years (49%), work as homemakers (32.7%), and are married (63.3%). The three most common complaints experienced by subjects with early-stage ovarian cancer were abdominal/pelvic pain (23.8%), abdominal/pelvic pressure (28.6%), and abdominal distension (42.9%), while in patients with advanced-stage ovarian cancer were abdominal/ pelvic pain (32.7%), abdominal distension (42.9%), and abdominal discomfort (bloating, early satiety, feeling of fullness, frequent belching, heartburn, nausea and vomiting) (44.2%). Conclusions: The three most common clinical complaints among patients before being diagnosed with early and advanced-stage ovarian cancer in the inpatient ward of Dr. Soetomo Regional General Hospital Surabaya in 2021 were similar. The recognition of these complaints and several risk factors are expected to assist in the earlier diagnosis of ovarian cancer.